The association of non-suicidal self-injurious and suicidal behaviors with religiosity in hospitalized Jewish adolescents. (October 2020) - Malkosh-Tshopp, Efrat; Ratzon, Roy; Gizunterman, Alex; Levy, Tomer; Ben-Dor, David H; Krivoy, Amir; Lubbad, Nesrin; Kohn, Yoav; Weizman, Abraham; Shoval, Gal
Religiosity may be a potent protective factor against self-injurious and suicidal behaviors. However, no previous study has addressed this relationship in adolescent psychiatric population. This study aimed to examine the association between religiosity and non-suicidal self-injurious (NSSI) and suicidal behaviors, among hospitalized Jewish adolescents. This is a cross-sectional study of 60 hospitalized Jewish adolescents in two mental health centers. They were evaluated for religiosity, NSSI, and suicidal behaviors. The following religiosity measures were found to be protective against NSSI: a higher degree of adherence to religious practices (extrinsic measure) (beta = −0.083, p = .006), a higher level of belief in religious principles (intrinsic measure) (beta = −0.063, p = .008) and a self-reported higher religious affinity (χ 2 = 7.64, p = .022). The severity of suicidal ideation inversely correlated with the extrinsic measure (standardized beta = −0.2, t = −2.5, p = .015) and with self-reported degree of religious affinity (analysis of variance, F = 3.5, p = .035). History of transition in religious affinity was associated with worse suicidal ideation (3.77 ± 1.8 vs. 2.26 ± 1.99, t = −3.25, p = .004) and with suicide attempts (OR = 3.89 (95% CI: 1.08 – 14.03), p = .004); however, these relationships were mediated by history of abuse. This study provides first evidence of a protective effect of some religiosity measures on NSSI and suicidal behaviors in hospitalized Jewish adolescents.